1998
DOI: 10.1523/jneurosci.18-04-01305.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptic Basis of GABAA,slow

Abstract: Although two kinetically distinct evoked GABAA responses (GABAA,fast and GABAA,slow) have been observed in CA1 pyramidal neurons, studies of spontaneous IPSCs (sIPSCs) in these neurons have reported only a single population of events that resemble GABAA,fast in their rise and decay kinetics. The absence of slow sIPSCs calls into question the synaptic basis of GABAA,slow. We present evidence here that both evoked responses are synaptic in origin, because two classes of minimally evoked, spontaneous and miniatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
144
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 54 publications
19
144
1
2
Order By: Relevance
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).…”
Section: Nih Public Accesssupporting
confidence: 92%
See 1 more Smart Citation
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).…”
Section: Nih Public Accesssupporting
confidence: 92%
“…Furosemide, when tested on 3 control neurons (in which no theta-bursts were given) did not significantly changed the RP of the IPSC (before furosemide application: 63.17 ± 0.59 mV & after furosemide application: 61.92 ± 0.46 mV; P > 0.05). This observation is consistent with those of (Banks et al, 1998;Jarolimek et al, 1996;Jarolimek et al, 1999;Ouardouz and Sastry, 2005;Pearce, 1993).Previous studies in our laboratory indicated that tetanic stimulations of inputs induce a shift in the RP for GABA-ergic PSCs of neonatal rat DCN neurons (Ouardouz and Sastry ., 2000;Ouardouz and Sastry., 2005) and neonatal rat hippocampal CA1 pyramidal neurons (Ouardouz et al, 2006). In DCN neurons, the tetanus-induced negative shift in the RP seems to be due to an increased expression and activation of KCC-2 through an activation of protein kinase A, protein synthesis and activation of protein phosphatases (Ouardouz and Sastry, 2005).…”
supporting
confidence: 90%
“…It has been proposed that these interneurons may be involved in the generation of slow GABA A receptor-mediated potentials (Pearce, 1993;Freund and Buzsáki, 1996;Banks et al, 1998). In line with this view it has been recently reported that in the CA3 subfield inhibitory events generated at dendritic sites have similar amplitudes but occurred less frequently and had slower kinetics than perisomatic events generated in stratum pyramidale (Bazelot et al, 2010).…”
Section: Interneurons As Gaba Releasing Nerve Cellsmentioning
confidence: 87%
“…These neurons were able to pace CA1 pyramidal cells at theta frequencies (Chap-man and Lacaille, 1999b). Two distinct GABA A IPSPs have been found, a fast one and slow one (Banks et al, 1998). The fast IPSP is important in gamma rhythms, whereas the slow IPSP has a time-scale similar to that of theta rhythms and could, therefore, be involved in theta oscillations (White et al, 2000).…”
Section: Network Oscillation Mechanismsmentioning
confidence: 98%